Union command failure in the Shenandoah : Major General Franz Sigel and the war in the Valley of Virginia, May, 1864 - Powell, David A. (David Alan), 1961- (Savas Beatie, 2019)
"Union Command Failure in the Shenandoah is an in-depth examination of Federal Major General Franz Sigel's campaign in the northern end of the Shenandoah Valley during the American Civil War, during May of 1864. General Sigel was ordered by Lieutenant General Ulysses S. Grant to conduct an offensive in conjunction with other Federal forces against the Confederate supply depot at Stanton, Virginia. Sigel was defeated in the Battle of New Market, May 15, 1864"--